The function of recurrent word-combinations in English translations from three different languages - Ebeling, Signe (Meta, 2022)
This article compares phraseological tendencies in translated vs. non-translated English through functionally classified 3-word sequences. The study builds on previous research that compared 3-grams in fiction texts originally written in English with fiction texts translated from Norwegian. The current investigation adds English translations from two additional languages – German and Swedish – with the aim of establishing to what extent the tendencies noted for English translations from Norwegian extend to English translations from other languages. Thus the study contributes to the discussion of translation universals and translation as a third code. At the level of 3-gram functions, it has been uncovered that English originals and translations share similar functional characteristics in eight of the fourteen categories identified. Of the remaining six, four show statistically significant differences between originals and translations, regardless of source language. Based on a more qualitative study of four specific 3-grams from two of these categories, it is concluded, in line with the previous studies, that the most likely explanations are source language(s) shining through and the (potentially universal) tendency for translators to use a smaller and more fixed set of expressions in their translations.